Useful Research for Students in T & I Institutions - Gile, Daniel (HERMES - Journal of Language and Communication in Business, 2001)
The usefulness of research in T&I training institutions is not a matter of course, and some efforts to find the optimum cost/benefit ratio in each environment is desirable. Gains can be sought in modest findings, enhanced reasoning skills and increased familiarity with scientific texts for students, and in higher academic status for the relevant institutions. Student research should not demand unreasonable investment in time and efforts. Students should benefit from close guidance, and collective work may have a multiplier effect on the benefit to be reaped from their investment. Empirical studies may be generally more suited to the students’ needs than theoretical work, and interdisciplinary projects should be contemplated with caution. Potentially useful projects in the T&I training environment can be sought inter alia in the following axes: literature analysis, language exploration, information loss and errors in Translation, Translation strategies, training and learning, quality perception.